MicroRNA target homeobox messenger RNA in HIV induced hematopoietic inhibition - Koka, Prasad S.; Ramdass, Bharathi (Frontiers in Cell and Developmental Biology, 2024)
Cytopenias are a common occurrence due to abnormal hematopoiesis persistent in patients suffering from and advancing with HIV/AIDS. In order to develop efficacious therapies against cytopenias, it is necessary to understand the mechanisms by which HIV infection affects the differentiation of hematopoietic stem-progenitor cells (HSPCs), causing hematopoietic inhibition, that leads to hematological disorders. Currently, only the antiretrovirals that are being used to treat HIV infection and indirectly lower the levels of virus replication also co-attenuate cytopenias. The evidence available suggests that this indirect efficacy may not prevail for the lifetime of the infected patients, and the acquired immunodeficiency can overtake the beneficial consequences of decreased virus replication. As cited in this article, we and our colleagues are the first to make a foray into the involvement of microRNAs and their use as potential interventional treatments for the cytopenias that occur with HIV/AIDS. Herein, we progressed further in the direction of the mechanisms of the involvement of homeobox gene regulation to cause cytopenias. We had previously shown that HIV-1 inhibits multi-lineage hematopoiesis of the CD34+ cells using SCID-hu Thy/Liv animals in vivo. Furthermore, we demonstrated that the virus-induced hematopoietic inhibition occurred despite the CD34+ cells being resistant to HIV-1 infection. We set out to search for the specific host factors secreted by CD4+ T-cells that likely participate in the inhibition of hematopoiesis of the HIV infection-resistant CD34+ cells. More recently, we reported the identification of virus-infected CD4+ thymocyte-secreted miRNA-15a and miRNA-24 and that their differential expression following HIV infection causes the indirect inhibition of hematopoiesis. We then hypothesized that the observed miRNA differential expression in the virus-infected T-cells causes the abnormal regulation of homeobox (HOX) gene-encoded transcriptomes in the CD34+ cells, affecting specific MAPK signaling and CD34+ cell fate, thereby disrupting normal hematopoiesis. We present that in HIV infection, miRNA-mediated post-transcriptional dysregulation of HOXB3 mRNA inhibits multi-lineage hematopoiesis, which translates into hematological disorders in virus-infected patients with HIV/AIDS. These observations portend specific microRNA candidates for potential efficacy against the virus-induced cytopenias that are otherwise not treatable by the existing HAART/ART regimens, which are primarily designed and applicable for the attenuation of virus replication.